1999
DOI: 10.1002/j.0022-0337.1999.63.5.tb03288.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of an extramural education program on the perceived clinical competence of dental hygiene students

Abstract: The purpose of this study is to evaluate the effect of an extramural rotation on dental hygiene student self‐perceptions of competence in specific clinical areas. Dental hygiene students attending one midwestern university from 1992 through 1998 rated their perceived level of competence on nineteen dimensions of dental hygiene practice prior to beginning a four‐week extramural rotation and again at the completion of the rotation. Results indicated that student perceptions of competence improved significantly o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Previous studies have shown that rotations increase student motivation as well as confidence and efficiency in their clinical skills. These benefits are achieved by increasing the number and type of patients the students see, demonstrating to them the kinds and levels of disease found in community settings and giving them the experience of working in a dental team setting 1 , 2 , 4 , 5 , 7 , 10 , 11 , 17 . Outside the United States, community rotations associated with dental education are often initiated with government collaboration or support to engage dental students in the provision of dental care for underserved patients, to help address the lack of access to a basic level of dental services, 11 – 15 and to help provide sustainable dental care to the underserved, even in rural areas.…”
mentioning
confidence: 99%
“…Previous studies have shown that rotations increase student motivation as well as confidence and efficiency in their clinical skills. These benefits are achieved by increasing the number and type of patients the students see, demonstrating to them the kinds and levels of disease found in community settings and giving them the experience of working in a dental team setting 1 , 2 , 4 , 5 , 7 , 10 , 11 , 17 . Outside the United States, community rotations associated with dental education are often initiated with government collaboration or support to engage dental students in the provision of dental care for underserved patients, to help address the lack of access to a basic level of dental services, 11 – 15 and to help provide sustainable dental care to the underserved, even in rural areas.…”
mentioning
confidence: 99%